PENGARUH VARIASI WAKTU FERMENTASI TERHADAP KADAR BIOETANOL CAMPURAN KULIT JERUK DAN KULIT NANAS - Abdul Qodril Azizy; Dian Anisa Rokhmah Wati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the effect of fermentation time on the bioethanol yield derived from orange peels, pineapple peels, and their combined substrates, while also evaluating the potential utilization of fruit peel waste as a sustainable bioenergy resource. Fermentation durations of 2, 4, and 6 days were systematically examined to determine the optimal condition for maximizing bioethanol production. An experimental quantitative approach was employed under controlled laboratory conditions. The bioethanol production process comprised feedstock preparation, acid hydrolysis using hydrochloric acid (HCl), fermentation facilitated by Saccharomyces cerevisiae, and subsequent distillation at 78°C. Fermentation time was treated as the independent variable, whereas bioethanol concentration served as the dependent variable. The ethanol content was measured using a refractometer and analyzed through a descriptive quantitative framework. The results demonstrate that fermentation time significantly influences bioethanol production. The highest bioethanol concentrations were achieved at 2 days of fermentation, yielding 11% for orange peels, 12% for pineapple peels, and 15% for the mixed substrate. Prolonged fermentation led to a decline in ethanol yield, which can be attributed to reduced microbial activity and substrate depletion. Despite these findings, the resulting bioethanol did not meet the Indonesian National Standard (SNI) for fuel-grade ethanol, indicating the necessity for further purification processes and optimization of fermentation conditions, Keywords: bioethanol, orange peel, pineapple peel, fermentation time.